MINIMALLY INVASIVE TECHNOLOGIES OF TREATMENT OF NON-VARICOSE ESOPHAGOINTESTINAL GASTRIC BLEEDING - К. G. Kubachev; Е. U. Kachesov; О. A. Petropavlovskaya; O. S. Danilin; D. A. Tvorogov (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The enhancement of direct results of treatment in patients with a bleeding gastro-duodenal ulcer and the Mallory–Weise syndrome using endoscopic and endovascular methods of hemostasis.MATERIAL AND METHODS. In this paper, the treatment results of the 253 patients with Mallory–Weise syndrome and the results of the 1063 patients with a bleeding gastro-duodenal ulcer are analyzed.RESULTS. An endoscopic hemostasis was conducted for all patients with a Mallory–Weise syndrome. For patients with bleeding ulcer: the injection therapy and unipolar coagulation were done for 238 patients (the bleeding recurrence was detected in 21 cases (8.8 %)); the injection therapy and argon plasma therapy were conducted for 341 patients (the bleeding recurrence was detected in 19 cases (5.6 %)); the injection therapy and clipping of vessels were conducted for 236 patients (the bleeding recurrence was detected in 11 cases (4.7 %)); the ulcer ligation was done for 98 patients without bleeding recurrences. 151 persons were treated only with the conservative treatment, while the recurrence was detected with 49 persons (32.5 %). The primary surgical treatment was done for 46 (4.3 %) patients, who had the traces of a heavy blood loss but it was not possible to visualize its source. Two patients died. 106 patients underwent an X-ray endovascular surgical procedure aimed at reaching the hemostasis. 100 patients of them had a bleeding recurrence and 6 of them had a comorbidity index over 30 points and a high risk of bleeding recurrence. One person with an acute cardiac insufficiency died.CONCLUSION. The bleeding recurrence and a high comorbidity index provide an evidence for undertaking X-ray endovascular method of hemostasis.